From foundling homes to day care: a historical review of childcare in Chile - A Rodrigo; René van der Veer; Harriet J. Vermeer; Marinus H. van IJzendoorn (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
This article discusses significant changes in childcare policy and practice in Chile. We distinguish four specific periods of childcare history: child abandonment and the creation of foundling homes in the 19th century; efforts to reduce infant mortality and the creation of the health care system in the first half of the 20th century; an increasing focus on inequality and poverty and the consequences for child development in the second half of the 20th century; and, finally, the current focus on children's social and emotional development. It is concluded that, although Chile has achieved infant mortality and malnutrition rates comparable to those of developed countries, the country bears the mark of a history of inequality and is still unable to fully guarantee the health of children from the poorest sectors of society. Recent initiatives seek to improve this situation and put a strong emphasis on the psychosocial condition of children and their families.